2018
DOI: 10.1002/eat.22963
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of weight control behavior persisting beyond young adulthood: Results from a 15‐year longitudinal study

Abstract: Objective: Dieting and unhealthy weight control behaviors have been associated with negative outcomes. Most research has examined the prevalence of these behaviors in adolescence and young adulthood. Less is known about whether they persist further into adulthood. We examined patterns of weight control behaviors beyond young adulthood using data from 1,455 males and females participating in Project EAT (Eating and Activity in Teens and Young Adults), a 15-year population-based, longitudinal study. Method: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Moreover, results indicated that restrictive eating may be more closely related to suicidal behaviors than other ED behaviors. This is particularly concerning because restrictive eating is common among people with EDs (Elran‐Barak et al, ) and among people in non‐clinical samples (Haynos et al, ; Neumark‐Sztainer, Wall, Larson, Eisenberg, & Loth, ). Indeed, in our sample, more subjects endorsed restrictive eating than any other ED behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, results indicated that restrictive eating may be more closely related to suicidal behaviors than other ED behaviors. This is particularly concerning because restrictive eating is common among people with EDs (Elran‐Barak et al, ) and among people in non‐clinical samples (Haynos et al, ; Neumark‐Sztainer, Wall, Larson, Eisenberg, & Loth, ). Indeed, in our sample, more subjects endorsed restrictive eating than any other ED behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…For Project EAT-IV, invitations were sent only to participants who had completed surveys at either or both Times 2 and 3 (Time 4; 2015–2016; n = 1,830; mean age = 31.0 ± 1.6 years), and accordingly, responders represent only 50% of those with usable contact information from baseline. Additional details of the methodology have been published previously (Haynos et al, 2018; Neumark-Sztainer, Wall, Eisenberg, Story, & Hannan, 2006; Neumark-Sztainer, Wall, Larson, Eisenberg, & Loth, 2011). All study protocols were approved by the University of Minnesota’s Institutional Review Board Human Subjects Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Body image concerns and eating pathology, including dysfunctional eating attitudes (e.g., giving too much time and thought to food and appearance) and behaviours (e.g., binging and purging), are core to the maintenance of eating disorders [2]. However, such eating pathology and body issues are common in the non-clinical population [3]. Epidemiological studies report that eating disorders are highly prevalent worldwide, especially in women from Western and westernized countries [4].…”
Section: Introductionmentioning
confidence: 99%